HUBUNGAN KUALITAS PELAYANAN KADER DENGAN KEPATUHAN KUNJUNGAN IBU BALITA KE POSYANDU DI DESA GASARIBU KECAMATAN LAGUBOTI KABUPATEN TOBA SAMOSIR - Butar-butar, Doortua (Jurnal Keperawatan Priority, 2018)
The health system can function optimally if supported by empowering people and as a form of empowerment is their guidance Posyandu cadre and mothers who bring their babies to Posyandu. Guidance cadres would improve their knowledge so that changing the behavior for implementation of knowledge. The purpose of this study was to analyze the relationship between service quality and compliance cadres with a visit to Posyandu toddler's mother in the village of Gasaribu District of Laguboti Toba Samosir. The study design used is cross sectional. The population mothers with toddlers were registered in the region of in the village of Gasaribu District of Laguboti Toba Samosir with a sample size of 50 respondents. Independent variable is the quality of service cadre, while the dependent variable is the compliance visit to the Posyandu toddler's mother. Measuring instrument uses closed questionnaire to measure guidance and registers Posyandu cadres Posyandu to measure compliance visit to the Posyandu toddler's mother. Data were analyzed with chi square test Results: There was a significant correlation between the quality of service cadres with compliance visits mothers (p = 0.005). Posyandu already actively supported also by the mother's educational background is sufficient. Guidance given Posyandu cadres can encourage mothers to come to Posyandu. The cadre who has worked with both fast and precise, and further enhance’ its services, especially in the field of service quality cadres.